The Effect of Parachute Training on Running Speed in Football - Agus Darmawan; Yogi Adi Nugroho (Universitas Negeri Semarang, 2026)
This study aims to determine the effect of training using parachutes on the running speed of SSB PS Peraga U-17 players using the Two Group Pretest-Posttest Design. Speed is an important component in football that supports a player's sprint and acceleration abilities. Parachute training includes resisted sprint training whichprovides air resistance so as to increase the work of the leg muscles when running. The method of this study was a quantitative experiment with two groups, namely the experimental group that was given training using a parachute and the control group that was not given special treatment. The research sample was SSB PS Peraga U-17 players who were selected with a total sampling technique. The research instrument used a 40-meter sprint running test conducted before and after the treatment. The results showed that the experimental group experienced a more significant increase in running speed than the control group. Thus, training using parachutes has an effect on increasing the running speed of SSB PS Peraga U-17 football players